2022
DOI: 10.1021/acs.jafc.1c07390
|View full text |Cite
|
Sign up to set email alerts
|

Production, Characterization, Delivery, and Cholesterol-Lowering Mechanism of Phytosterols: A Review

Abstract: Phytosterols are natural plant-based bioactive compounds that can lower blood cholesterol levels and help prevent cardiovascular diseases. Consequently, they are being utilized in functional foods, supplements, and pharmaceutical products designed to improve human health. This paper summarizes different approaches to isolate, purify, and characterize phytosterols. It also discusses the hypolipidemic mechanisms of phytosterols and their impact on cholesterol transportation. Phytosterols have a low water-solubil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 120 publications
0
41
0
1
Order By: Relevance
“…Nanoparticles are a material with a particle size from 10 to 1000 nm [ 70 ]. Compared with other delivery systems, nanoparticles have many advantages [ 71 , 72 ], which are widely used in food, medicine, and other fields [ 73 , 74 , 75 ]. The nanoparticle technology in the functional food field mainly focuses on the delivery of active substances such as lutein, astaxanthin ester, and curcumin [ 76 ].…”
Section: Delivery Systems Of Dhamentioning
confidence: 99%
“…Nanoparticles are a material with a particle size from 10 to 1000 nm [ 70 ]. Compared with other delivery systems, nanoparticles have many advantages [ 71 , 72 ], which are widely used in food, medicine, and other fields [ 73 , 74 , 75 ]. The nanoparticle technology in the functional food field mainly focuses on the delivery of active substances such as lutein, astaxanthin ester, and curcumin [ 76 ].…”
Section: Delivery Systems Of Dhamentioning
confidence: 99%
“…FTIR spectrometry and circular dichroism spectroscopy were conducted to further determine the alteration in protein secondary structure for the qualitative analysis ( 49 ). Amide band, consisting of amide I, amide II, and amide III, is the characteristic band for studying protein structures.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, G 0 <0 indicated that the combination of SPI and β-carotene was spontaneous (48), which re-supported the last speculation in section "Bonding mode analysis." Frontiers in Nutrition 08 frontiersin.org secondary structure for the qualitative analysis (49). Amide band, consisting of amide I, amide II, and amide III, is the characteristic band for studying protein structures.…”
Section: Thermodynamic Property Analysismentioning
confidence: 99%
“…It has been estimated that 100-500 mg d −1 of phytosterol is consumed in different regions of the globe which is supplied from basic diet, functional food, nutrition supplements, and pharmaceutical products [37]. Phytosterols are produced mostly from plant extract such as vegetable oils, grains, and nuts [38]. Economical sources of phytosterol extraction have been under investigation from various sources including red and brown algae [39].…”
Section: Discussionmentioning
confidence: 99%